Facilitating the implementation of Open Science practices across Africa - Mchunu, Nokuthula P.; Masisi, Keletso (My University, 2024)
This session is part of the AfricArXiv Webinar Series on Open Science for the Discoverability of African Research.
Watch the recording https://africarxiv.pubpub.org/pub/gbtxduev#nbshhxs5t7c
Keywords: Open science; Africa; Open Science Platform